A4NH 2019 annual report highlights: Flagship 5 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
This includes three highlights document for Flagship 5 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: A4NH joins partners to launch new CGIAR antimicrobial resistance hub Highlight 2: Harmonizing agricultural intensification and climate change mitigation Highlight 3: Connecting research with policy to achieve results on critical diseases